WHO ARE WE IN A GLOBALIZED WORLD? NATIONAL IDENTITY AND CULTURAL SUSTAINABILITY OF CONTEMPORARY UKRAINE - Zaichko, Vladyslava (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2024)
B a c k g r o u n d . The article delves into the urgent and complex issue of national identity in the era of globalization, with a specific focus on Ukraine. While globalization brings about positive changes such as cultural exchange and international cooperation, it also poses a significant risk of erasing national borders and diluting identity. The crucial role of language and culture as the core elements of identity is underscored, along with the challenges that Ukraine has confronted due to war and external information aggression. M e t h o d s . The work uses an interdisciplinary approach that combines philosophical, sociological, and culturological analysis. The main methods are comparative analysis to compare the concepts of identity, contextual interpretation to study the functioning of the term "national identity" in different texts, and lexical and semantic analysis to study the linguistic means of expressing identity. A critical analysis of cultural narratives and strategies of information influence was used. R e s u l t s . The analysis showed that national identity is a multifaceted phenomenon that includes linguistic, cultural, territorial, and historical aspects. Globalization enhances integration and destructive processes in forming identity. The article emphasizes that language is a critical factor in preserving national identity. It considers the impact of information wars and manipulative strategies on undermining identity and the need to implement effective language and cultural policies to consolidate Ukrainian society. C o n c l u s i o n s . Globalization presents both opportunities and risks for national identity. The delicate balance between global integration and cultural preservation is crucial for Ukraine. The conscious development of language, culture, and education is a key factor in shaping national identity. The article stresses the importance of devising strategies to bolster national consciousness and counter external challenges, particularly information threats. The findings of this study can serve as a valuable resource for further research on identity in philosophical, sociological, and cultural contexts.